SARS-Cov-2 Viral Kinetics in Mild COVID-19 Patients Treated with Chloroquine Regimens or Standard of Care - Siripassorn, Krittaecho; T. Huang, Angkana; Nitiyanontakij, Ravee; Uttayamakul, Sumonmal; Klungthong, Chonticha; Hunsawong, Taweewun; Rungrojcharoenkit, Kamonthip; Lohachanakul, Jindarat; Kodchakorn, Chanikarn; Vanachayangkul, Pattaraporn; Poolpanichupatum, Yongyuth; Hussem, Kittinun; et al. (International Journal of Coronaviruses, 2021)
This study measures the impact of chloroquine (CQ) therapy in reducing SARS-CoV-2 viral load in infected individuals and hence its transmissibility by describing changes in nasopharyngeal SARS-CoV-2 RNA kinetics in patients receiving standard of care (SOC) or CQ +/- ritonavir-boosted lopinavir (LPV/r). The nasopharyngeal (NP) samples were collected from mild COVID-19 patients admitted at Bamrasnaradura Infectious Diseases Institute between March and April of 2020. These patients either received SOC, or a high dose of CQ with loading dose, or high dose of CQ plus LPV/r. The samples were tested at AFRIMS using a quantitative RT-PCR assay. Levels of CQ in the plasma were measured 6 days post initiation of their treatment. In some instances, viral isolation was attempted to determine SARS-CoV-2 viability. Analyses of the clinical outcomes showed that CQ +/- lopinavir did not contribute significantly to decreasing the number of days with detected SARS-CoV-2 RNA. Viral NP GEs declined faster in the CQ group, but benefits diminished rapidly with delays in treatment initiation. Funding Global Emerging Infections Surveillance, Armed Forces Health Surveillance Branch (GEIS-AFHSB) for all research-related activities at the AFRIMS
Keywords: Chloroquine; COVID-19; SARS-CoV-2; viral kinetics; therapeutic.